Femtosecond X-ray-induced fragmentation of fullerenes. Issue 4 (21st February 2016) - Berrah, N.; Murphy, B.; Xiong, H.; Fang, L.; Osipov, T.; Kukk, E.; Guehr, M.; Feifel, R.; Petrovic, V.S.; Ferguson, K.R.; Bozek, J.D.; Bostedt, C.; et al.
Abstract : A new class of femtosecond, intense, short – wavelength lasers – the free-electron laser – has opened up new opportunities to investigate the structure and dynamics in many scientific areas. These new lasers, whose performance keeps increasing, enable the understanding of physical and chemical changes at an atomic spatial scale and on the time scale of atomic motion which is essential for a broad range of scientific fields. We describe here the interaction of fullerenes in the multiphoton regime with the Linac Coherent Light Source (LCLS) X-ray free-electron laser at SLAC National Laboratory. In particular, we report on new data regarding the ionization of Ho3 N@C80 molecules and compare the results with our prior C60 investigation of radiation damage induced by the LCLS pulses. We also discuss briefly the potential impact of newly available instrumentation to physical and chemical sciences when they are coupled with FELs as well as theoretical calculations and modeling.